Mechanical Strain Induces Transcriptomic Reprogramming of Saphenous Vein Progenitors - Maselli, Davide; Garoffolo, Gloria; Cassanmagnago, Giada Andrea; Vono, Rosa; Ruiter, Matthijs S.; Thomas, Anita C.; Madeddu, Paolo; Pesce, Maurizio; Spinetti, Gaia (Frontiers in Cardiovascular Medicine, 2022)
Intimal hyperplasia is the leading cause of graft failure in aortocoronary bypass grafts performed using human saphenous vein (SV). The long-term consequences of the altered pulsatile stress on the cells that populate the vein wall remains elusive, particularly the effects on saphenous vein progenitors (SVPs), cells resident in the vein adventitia with a relatively wide differentiation capacity. In the present study, we performed global transcriptomic profiling of SVPs undergoing uniaxial cyclic strain in vitro. This type of mechanical stimulation is indeed involved in the pathology of the SV. Results showed a consistent stretch-dependent gene regulation in cyclically strained SVPs vs. controls, especially at 72 hours. We also observed a robust mechanically related overexpression of Adhesion Molecule with Ig Like Domain 2 (AMIGO2), a cell surface type I transmembrane protein involved in cell adhesion. The overexpression of AMIGO2 in stretched SVPs was associated with the activation of the transforming growth factor β pathway and modulation of intercellular signaling, cell-cell, and cell-matrix interactions. Moreover, the increased number of cells expressing AMIGO2 detected in porcine SV adventitia using an in vivo arterialization model confirms the arterial-like mechanic upregulation of AMIGO2. These results show that mechanical stress promotes SVPs' molecular phenotypic switching and increases their responsiveness to extracellular environment alterations, thus prompting the targeting of new molecular effectors to improve the outcome of bypass graft procedure.